Pengaruh Psikoedukasi Terhadap Kadar Hormon Kortisol Pada Ibu Tujuan Dengan Depresi Postartum Di Wilayah Kerja Dinas Kesehatan Kota Langsa Tahun 2020 - Fithriany Fithriany; Cut Yuniwati; Silfia Dewi; Lili Kartika Sari Harahap (Syntax Corporation Indonesia, 2022)
Maternity mothers About 50-80% experience baby blues within ten days of giving birth. This is if the mother does not get further treatment then the baby blues can escalate into heavier depression. There is no definitive test yet that can determine a mother suffering from postpartum depression. This is why most postpartum depression sufferers are undiagnosed and do not get treatment early. Treatment that can be given to mothers who are depressed by providing health education, one of which is by providing psychoedukasi to the mother. The purpose of this study was to look at the influence of psychoedukasi on cortisol hormone levels in mothers with postpartum depression in the working area of Langsa City Health Office in 2020. This research uses quasi experimental design with the design of the one group pretest-posttest. Observations were made before and after the treatment of psychoedukasi,, The number of samples in this study as many as 16 mothers postpartum the second day with postpartum depression. The analyses used were the Wilcoxon Test and the Whitney Mann Test. The results showed the influence of decreased levels of the hormone cortisol before and after the administration of psychoedukasi with sig value. 0.00, there is a decrease in postpartum depression by administering psychoeducation with sig value. 0.000 and the effect of decreased cortisol levels on postpartum depression decrease with sig value. 0.00.